1996
DOI: 10.1007/s004270050031
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of annexin V during spermatogenesis in the newt Cynops pyrrhogaster

Abstract: In order to isolate genes whose expression is up-regulated after the initiation of meiosis, we screened a cDNA expression library of newt testes with antiserum against homogenates of testes derived from the spermatogonial and spermatocyte stages. We report the isolation of spermatocyte-specific cDNA clones encoding a newt homologue of the calcium-dependent phospholipid-binding protein, annexin V. Northern blot analysis showed that newt annexin V mRNA was 1.7 kb in length and was expressed strongly in testes, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In the previous study, we have shown that newt annexin V serves as a molecular marker to monitor the differentiation of spermatogonia into primary spermatocytes ( Yamamoto et al 1996 ). However, annexin V mRNA expression starts in primary spermatocytes during the leptotene–zygotene stages, when meiosis has already initiated.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous study, we have shown that newt annexin V serves as a molecular marker to monitor the differentiation of spermatogonia into primary spermatocytes ( Yamamoto et al 1996 ). However, annexin V mRNA expression starts in primary spermatocytes during the leptotene–zygotene stages, when meiosis has already initiated.…”
Section: Discussionmentioning
confidence: 99%
“…Poly(A) + -RNA was prepared from various tissues of adult newts as described above. Northern blot analysis was done as described previously (Yamamoto et al, 1996). Five microgram of poly(A) + -RNA was electrophoresed in a 1% formaldehyde agarose gel and blotted to a nylon-membrane, Hybond(N)+ (Amersham).…”
Section: Northern Blot Analysismentioning
confidence: 99%
“…Protein extraction and Western blot analysis using a monoclonal antibody against recombinant newt annexin V were performed as described previously (Yamamoto et al ., 1996). Ten micrograms of protein extracted from newt testis were separated by 12% SDS-PAGE, blotted onto PVDF membrane (Millipore), and treated with the anti-newt annexin V monoclonal antibody.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Previously, we isolated annexin V as a protein differentially expressed during newt spermatogenesis (Yamamoto et al ., 1996). Newt annexin V is abundantly expressed in the cytoplasm of primary spermatocytes and round spermatids.…”
Section: Introductionmentioning
confidence: 99%